If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5 = 0.4 + -0.25x Solving 0.5 = 0.4 + -0.25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.25x' to each side of the equation. 0.5 + 0.25x = 0.4 + -0.25x + 0.25x Combine like terms: -0.25x + 0.25x = 0.00 0.5 + 0.25x = 0.4 + 0.00 0.5 + 0.25x = 0.4 Add '-0.5' to each side of the equation. 0.5 + -0.5 + 0.25x = 0.4 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + 0.25x = 0.4 + -0.5 0.25x = 0.4 + -0.5 Combine like terms: 0.4 + -0.5 = -0.1 0.25x = -0.1 Divide each side by '0.25'. x = -0.4 Simplifying x = -0.4
| .666x+4=.666x-6 | | 180-96=x | | 6(-x+4)=x-12 | | -4(x-2)(x+1)=0 | | Sin(4x)*Sin(9x)=0 | | sin(4x)sin(9x)=0 | | 3(r-5)-2r=-11+3 | | b=1.2+3.6b | | 6-21=4x-7-3x | | -0.00016185t^4+0.0036148t^3-0.026868t^2+0.07258t-0.04537=0 | | 12-3x+10=7 | | -12x-15=x-12 | | 1.5-6h=-1.83 | | 7x-6x+12=13-5 | | 8m-(3m)=4 | | (2q+3)(2q-3)=0 | | -12n+12=11n-13 | | 5y-6x=4 | | 2x^2+3x-34=10 | | 4+12y=0 | | 3y+2x=120 | | 15x+4y=72 | | 66=6(m+3.1) | | -5r+6=-5(s+2) | | 7-7y=14 | | 0=-3x^2+12x-11 | | 8(x-3)-1(x-3)=0.7 | | 0.67(3q+6)=8 | | 15.00+2.00x=13 | | 11x-5=9x+13 | | 2(4x+1)=8+7x | | -3y-11=-5(y-1) |